Seneca's Tragedies and the Aesthetics of Pantomime - Zanobi, Alessandra (Criminal Practice Ser, 2014)
Title Page -- Also Available From Bloomsbury -- Table of Contents -- Introduction -- 1 Pantomime in the Ancient World -- 2 Pantomime and the Structure of Seneca's Tragedies -- 3 Pantomime and Descriptive Running Commentaries -- 4 Monologues of Self-analysis -- 5 Pantomime and Descriptive Narrative Set-pieces of Seneca's Tragedies -- Conclusion -- Notes -- References -- Index of Ancient Authors -- General Index -- Copyright.